2012
DOI: 10.1103/physrevb.85.195112
|View full text |Cite
|
Sign up to set email alerts
|

Charge-ordered spinel AlV2O4: High-energy-resolution EELS and computational studies

Abstract: The electronic and magnetic structure of the charge-ordered spinel AlV 2 O 4 is studied using a combination of high-energy-resolution electron energy-loss spectroscopy and density functional theory. We find that the vanadium atoms have a fractional valence close to 2.4+ and display a charge and magnetic ordering consistent with previous reports. The oxygen K edge features a prominent prepeak indicative of a strong hybridization of O 2p and V 3d hole states. Experiments at high temperatures confirm a structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…The oxygen K-edges show a three peak structure with peaks at 538(±1), 541(±1) and 546(±1) eV. These edge values compare well with the earlier observed [11] O K edge energies at 535, 540 and 545 eV and V-L 3 and V-L 2 peaks at 519 and 527 eV. The difference observed in the O 1s to hybridized 3 e g peak at 538(±1) eV from the literature quoted value (535 eV) is considered acceptable within the statistics [18].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The oxygen K-edges show a three peak structure with peaks at 538(±1), 541(±1) and 546(±1) eV. These edge values compare well with the earlier observed [11] O K edge energies at 535, 540 and 545 eV and V-L 3 and V-L 2 peaks at 519 and 527 eV. The difference observed in the O 1s to hybridized 3 e g peak at 538(±1) eV from the literature quoted value (535 eV) is considered acceptable within the statistics [18].…”
Section: Resultssupporting
confidence: 90%
“…The charge on Al remains the same in the cubic and in the rhombohedral phases. Very recently electron energy loss spectroscopy (EELS) measurements on AlV 2 O 4 [11] have estimated the average value of charge on vanadium to be 2.5 + . Thus, presently, there appears to be convergence on the heptamer structural model, but a consensus has yet to emerge on the assignment of charges on vanadium.…”
Section: Introductionmentioning
confidence: 99%
“…Our the differences in the charges between the ions V1, V2 and V3 should be small (see Table 1). A similar conclusion was reached by Prytz et al (2012). Another argument in favor of this conclusion is the proximity of electron density distributions for various V-O bonds in the rhombohedral modification of the AlV 2 O 4 structure (Fig.…”
Section: Crystal Chemistry Of the Alv 2 O 4 Rhombohedral Phasesupporting
confidence: 73%
“…In these works, it was shown that spin-polarization effects should be accounted for in order to reproduce the band structure. Chemical bonding was considered by Prytz et al (2012) using a difference study of electron density and full Bader analysis utilizing planewaves basis set and PBE exchange potential. However, Bader analysis may be inaccurate in the case of metallic bonds (Gatti & Macchi, 2012) with flat regions of electron density which complicates the search of critical points.…”
Section: Density Functional Study Of Charge Distribution and Bondingmentioning
confidence: 99%
“…The oxidation states of the transition metal oxides to a large extent determine their physiochemical properties. ELNES analysis of the EELS spectrum, with its special valence sensitivity to 3 d transition metals [44,45,46], is capable of revealing the electronic structure of target atoms (i.e., valence state, atomic coordination, and spin state). For instance, making use of the white line ratio ( L 3 / L 2 ) of the Cr- L 2,3 edge, a number of studies have successfully analyzed the oxidation state in chromium oxides [42,43,47].…”
Section: Resultsmentioning
confidence: 99%